Analysis of Trademark Cancellation for The Protection of The First Registrant's Trademark: BIOAQUA Study (Pandecta Research Law Journal, 2022)
Due to the cancellation of the BIOAQUA case in Decision Number: 618 K/Pdt.Sus-HKI/2020, the plaintiff did not receive the legal protection that he deserved. The study’s goal is to examine the legal protection afforded to the first trademark registration applicant in the BIOAQUA trademark case, followed by an examination of the judge’s decision to cancel the BIOAQUA trademark. This study is normative and legal in nature. The research strategy is a case study approach. The data source is secondary data, and the data analysis is qualitative. The findings revealed that in the case of the BIOAQUA trademark, legal protection is provided to the first applicant of trademark registration against the defendant. Because the judge considers the same as the authority under Article 3 of Law No. 20 of 2016 concerning Trademarks and Geographical Indications, the plaintiff is not considered the first registrant. The judge’s consideration in the BIOAQUA trademark cancellation case is based on Articles 76 and 77 of Trademarks and Geographical Indications Law No. 20 of 2016. The judge considers the content of Article 76, namely that cancellation can be made against registered trademarks, but because the element of good faith cannot be proven, the defendant’s trademark is not cancelled, and the legal effect of this is that the defendant’s BIOAQUA trademark is protected by registered trademarks.